Yeasts from Nanfeng mandarin plants: occurrence, diversity and capability to produce indole-3-acetic acid - Xuan Peng; Ya Wang; Li Juan Tang; Xi Xi Li; Yi Wen Xiao; Zhi Bin Zhang; Ri Ming Yan; Hui Lin Yang; Jun Chang; Bo Zhu; Du Zhu (Biotechnology & Biotechnological Equipment, 2018)
Plant growth promoters produced by microorganisms can play a significant role in the induction of some important physiological responses in the growth and development of plants. In this study, we provided a first insight into revealing the diversity of cultivable yeasts associated with Nanfeng mandarin (Citrus reticulata cv. Blanco) in China. Their capability to produce indole-3-acetic acid (IAA) was analyzed. A total of 796 yeast strains were obtained by the enrichment isolation technique from citrus soil, citrus leaves, citrus peel and citrus pulp of Nanfeng mandarin samples. On the basis of the 26S rDNA partial sequence analysis, the strains were identified as 14 yeast species in 9 genera belonging to Hanseniaspora sp., Pichia sp., Candida sp., Sporidiobolus sp., Meyerozyma sp., Symmetrospora sp., Rhodotorula sp., Starmerella sp. and Aureobasidium sp. The most abundant species in citrus soil were Starmerella meliponinorum and Meyerozyma caribbica. The species prevailing in citrus peel was Hanseniaspora opuntiae. Citrus pulp was rich in Meyerozyma guilliermondii. Additionally, Aureobasidium pullulans and H. opuntiae were the dominant species in citrus leaves. All yeast species obtained were accessed for the capability to produce IAA: 26 strains in seven species showed the capability of producing IAA. Rhodotorula paludigena produced the highest IAA concentrations of 76.22 mg/L. Our study confirms the phylogenetic diversity of yeast associated with Nanfeng mandarin and highlights that these yeast strains are promising resources of microbial fertilizer.